The miR-148/152 family contributes to angiogenesis of human pluripotent stem cell- derived endothelial cells by inhibiting MEOX2 - Fengyue Ding; Hongchun Wu; Xinglong Han; Xue Jiang; Yang Xiao; Yuanyuan Tu; Miao Yu; Wei Lei; Shijun Hu (Elsevier, 2023)
Human pluripotent stem cell-derived endothelial cells (hPSC-ECs) represent a promising source of human ECs urgently needed for the study of cardiovascular disease mechanisms, cell therapy, and drug screening. This study aims to explore the function and regulatory mechanism of the miR-148/152 family consisting of miR-148a, miR-148b, and miR-152 in hPSC-ECs, so as to provide new targets for improving EC function during the above applications. In comparison with the wild-type (WT) group, miR-148/152 family knockout (TKO) significantly reduced the endothelial differentiation efficiency of human embryonic stem cells (hESCs), and impaired the proliferation, migration, and capillary-like tube formatting abilities of their derived ECs (hESC-ECs). Overexpression of miR-152 partially restored the angiogenic capacity of TKO hESC-ECs. Furthermore, the mesenchyme homeobox 2 (MEOX2) was validated as the direct target of miR-148/152 family. MEOX2 knockdown resulted in partial restoration of the angiogenesis ability of TKO hESC-ECs. The Matrigel plug assay further revealed that the in vivo angiogenic capacity of hESC-ECs was impaired by miR-148/152 family knockout, and increased by miR-152 overexpression. Thus, the miR-148/152 family is crucial for maintaining the angiogenesis ability of hPSC-ECs, and might be used as a target to enhance the functional benefit of EC therapy and promote endogenous revascularization.